Collider signatures of Higgs-portal scalar dark matter - Huayong Han; Jin Min Yang; Yang Zhang; Sibo Zheng (Physics Letters B, 2016)
In the simplest Higgs-portal scalar dark matter model, the dark matter mass has been restricted to be either near the resonant mass (mh/2) or in a large-mass region by the direct detection at LHC Run 1 and LUX. While the large-mass region below roughly 3 TeV can be probed by the future Xenon1T experiment, most of the resonant mass region is beyond the scope of Xenon1T. In this paper, we study the direct detection of such scalar dark matter in the narrow resonant mass region at the 14 TeV LHC and the future 100 TeV hadron collider. We show the luminosities required for the 2σ exclusion and 5σ discovery.